Perkembangan asas-asas hukum pidana Indonesia : perspektif perbandingan hukum pidana - Arief, Barda Nawawi, 1943- (Semarang : Badan Penerbit Undip, 2010)
On principles of the criminal law as enacted in Indonesian Criminal Code; includes comparison of criminal laws of various countries.
Keywords: Criminal law -- Indonesia; Criminal law